Prevalence of Iron Deficiency Anemia Among Children - Ikhtiyorov Shakhboz Ikhtiyor Ugli (International Journal on Orange Technologies, 2020)
As a material of the research, 40 patients with iron deficiency were taken from 50 patients who were treated in the Hematology Department of the children's multidisciplinary medical center of Khorezm region. We divided the patients treated with iron deficiency anemia into 3 groups according to the degree of the disease (Table 1) as well as the origin (Table 2). We divided the patients into two groups during the study. Group 1) 20 patients were told to take the prescribed medications, mainly with tea, to themselves or their mother. Group 2) 20 patients were told to take the prescribed medications mainly with boiled water, to themselves or their mother.